Early morning salivary cortisol and cortisone, and adrenal responses to a simplified low‐dose short Synacthen test in children with asthma. (5th September 2013) - Blair, Joanne; Lancaster, Gillian; Titman, Andrew; Peak, Matthew; Newlands, Paul; Collingwood, Catherine; Chesters, Christine; Moorcroft, Teresa; Wallin, Naomi; Hawcutt, Daniel; Gardner, Christopher; Didi, Mohammed; et al.
Abstract Objective To examine serum cortisol responses to a simplified low‐dose short Synacthen test (LDSST) in children treated with inhaled corticosteroids (ICS) for asthma and to compare these to early morning salivary cortisol (EMSC) and cortisone (EMSCn) levels. Design Early morning salivary cortisol and EMSCn samples were collected for three consecutive days. On day three, Synacthen 500 ng/1·73 m2 was administered intravenously. Samples were collected at 0, 15, 25, 35 min. Results A total of 269 subjects (160 M: 109 F), median (range) age 10·0 (5·1–15·2) years were studied. Peak cortisol in the LDSST was <500 nmol/l in 101 subjects (37·5%) and <350 nmol/l in 12 subjects (4·5%). Basal cortisol correlated with peak cortisol: r = 0·55, (95% CI: 0·46, 0·63, P < 0·0001). Time at which peak cortisol concentration was achieved was significantly related to the value of peak cortisol (P < 0·0001), with higher cortisol peaks occurring later in the test and lower cortisol peaks occurring earlier. EMSC and EMSCn had no predictive value for the identification of patients with a peak cortisol <500 nmol/l. EMSCn was superior to EMSC in identifying patients with a peak cortisol <350 nmol/l: a minimum EMSCn cut‐off value of 12·5 nmol/l gave a negative predictive value of 99·2% and positive predictive value of 30·1%. Conclusion Our data illustrate that basal measures of cortisol are likely to be of value in screening populations for patients at greatest risk of adrenal crisis. EMSCn shows promise as a screening tool for the identification of patients with severe adrenal insufficiency.